Fillers and Reinforcements for Advanced Nanocomposites - Dong, Yu; Umer, Rehan; Lau, Alan Kin-Tak (Woodhead Publishing series in composites science and engineering, 2015)
This book reviews cutting-edge, state-of-the-art research on the effective use of nanoscaled fillers and reinforcements to enhance the performance of advanced nanocomposites, both in industrial and manufacturing applications. It covers a broad range of topics such as nanocelluloses, nanotubes, nanoplatelets, and nanoparticles, as well as their extensive applications. The chapters provide detailed information on how fillers and reinforcements are used in the fabrication, synthesis and characterization of advanced nanocomposites to achieve extraordinary performance of new materials and significant enhancements in their mechanical, thermal, structural and multi-functional properties. It also highlights new technologies for the fabrication of advanced nanocomposites using innovative electrospinning techniques.